Proposed Marketing Strategy to Increase Sales of Selaras Outdoor - Rhadinda Rhesaudrina Diva (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
Selaras Outdoor is a family-based restaurant established in Ciamis in 2021. The F&B business sells affordable prices with a variety of Sundanese and western food products. The location of Selaras Outdoor focuses on nature as if enjoying a meal in a small private forest with the sound of nature from a flowing river. Knowing the increasing number of new restaurants/cafes with outdoor themes, Selaras Outdoor faces business problems that occur including sales revenue that continues to fall. The number of visitors who come is decreasing due to the habit of Ciamis and Tasikmalaya residents who will visit when a new restaurant or cafe location opens. Therefore, a strategy is needed to be able to increase revenue which starts from customer satisfaction. The findings from this research will be used to get the best marketing strategy to create a way to increase revenue. Therefore, a research study will be conducted to address the problems experienced by Selaras Outdoor. The business exploration of Selaras Outdoor will be developed based on external (PESTEL, Porter's Five Forces, customers, and competitors) and internal (VRIO, STP, and Service Marketing Mix) analysis. This research uses two types of data, namely primary and secondary data. Primary data will be collected through interviews and observations while secondary data is carried out to strengthen the theoretical basis of each variable studied as well as external and internal analysis in this study. By using triangulation of data collection on what has been obtained from customers who have visited Selaras Outdoor as well as the latest news sources regarding outdoor restaurants, the results show that customer satisfaction has a positive effect on Selaras Outdoor. Based on the external and internal analysis, the researcher conducted a SWOT analysis and identified the root of the problem. From there it developed into several strategies that were combined together to produce two strategies. The researcher recommended one best strategy with weaknesses that can be overcome to overcome the root causes.